Surface Modification of the Improved Stainless Steel Alloy AISI-304 and the Use of Diffusion Coating and a Study of Its Efficiency in Resistivity Hot Corrosion in an Atmosphere of Sodium Chloride Vapor NaCL and Sodium SulfateNa_2 SO_4 (Baghdad Science Journal, 2024)
This research aims to modify the components of stainless steel alloy by the method of surface engineering through the single diffusion coating technique in order to obtain new alloys with high efficiency in resisting harsh environmental conditions. Steam a mixture of sodium chloride ( ) and sodium sulfate ( ) at a temperature of 900 and then compare it with the base alloy. The results showed that the alloys produced in this way are very efficient. The results showed that the aluminum coating showed high efficiency in resisting oxidation and provided better protection for a longer time compared to the uncoated alloy due to the  oxide crust layer formed with high adhesion as well as the aluminum-rich phases, whether the phases were nickel-aluminum or iron-aluminum. The results also showed that the thickness of the coating and the weight gain of the alloy is subject to the parabola relationship with time.